2015
DOI: 10.1186/s13018-015-0276-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical and radiologic treatment outcomes of Kienböck’s disease

Abstract: PurposeThe clinical outcomes of scaphotrapeziotrapezoid (STT) arthrodesis were compared to radial shortening osteotomy (RSO) to determine if any of the treatment methods was superior. The impact of RSO and vascularized bone grafts (VBG) on disease progression were measured based on X-rays to evaluate if a difference in Kienböck’s disease (KD) progression exists.MethodsOut of 98 consecutive patients treated between 1991 and 2013, 46 had STT arthrodesis, 21 had RSO, 7 had VBG, and 3 had VBG and RSO. Patients tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Moreover, the results of various clinical studies on the patients with Kienbock's disease treated with radius shortening showed that the pain decreased in this group of the subjects following-up a long period of time (up to 18 years). 12,14,18 Moreover, grip force and quality of life increased significantly. This may be due to the effects of radius shortening on joint contact force (actually pain decreased due to decrease in joint contact force).…”
Section: Loading (Mpa)mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the results of various clinical studies on the patients with Kienbock's disease treated with radius shortening showed that the pain decreased in this group of the subjects following-up a long period of time (up to 18 years). 12,14,18 Moreover, grip force and quality of life increased significantly. This may be due to the effects of radius shortening on joint contact force (actually pain decreased due to decrease in joint contact force).…”
Section: Loading (Mpa)mentioning
confidence: 99%
“…17 It seems that there is no significant difference between wrist pain, grip strength between scaphoid-trapezoid-trapezium arthrodesis, and radial-shortening operation. 18 No evidence supports the efficacy of vascularization over decompression or both. 18 There is no doubt that the outcome of the treatment used for this disease depends on intra-articular joint pressure reduction.…”
mentioning
confidence: 99%
See 1 more Smart Citation